1981
DOI: 10.2355/isijinternational1966.21.812
|View full text |Cite
|
Sign up to set email alerts
|

Process Factors for Cold-rolled Dual-phase Sheet Steels

Abstract: Dual phase structure formation in the intercritical annealing method is strongly affected by the cooling stage. Role of the cooling stage consists of 1) carbon enrichment into the untransformed austenite, 2) avoidance of pearlite formation, and 3) martensite and retained austenite formation. Significance of a two-stage cooling can be explained on the above basis. Employment of a rapid heating and a short-time intercritical holding produces a dual phase steel having both a high bake-hardening and a high work-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The open symbols represent conventional CG dual phase steels and the closed ones are available data on UFG dual phase steels. 12,13,18,26,27,[32][33][34][35] The results for UFG dual phase structures in this study are comparable to those reported in the literature. These data are at or above the upper limit for the balance in CG dual phase steels depicted by the solid line.…”
Section: Discussionsupporting
confidence: 86%
“…The open symbols represent conventional CG dual phase steels and the closed ones are available data on UFG dual phase steels. 12,13,18,26,27,[32][33][34][35] The results for UFG dual phase structures in this study are comparable to those reported in the literature. These data are at or above the upper limit for the balance in CG dual phase steels depicted by the solid line.…”
Section: Discussionsupporting
confidence: 86%
“…60) Additionally, the increasing fraction of retained austenite stemming from the higher carbon content in austenite was shown to be important for the improved ductility. 61) In the present case, slower cooling leads to the break-up of large martensite islands and martensite bands, hence, yielding a fine martensite distribution that cannot be achieved by lowering the intercritical annealing temperature or holding time. Generally, a fine martensite dispersion is desirable for good formability properties.…”
Section: Implications For Mechanical Propertiesmentioning
confidence: 69%
“…[10] Because there is no additional process step required, BH could result in good shape fixability and improved dent and crash resistance without compromising the production cost. [9] In an earlier study of the BH mechanism, [15] it was proposed that the increase in the yield strength in the DP steels after treatment was caused by the presence of mobile dislocations formed in ferrite around the dispersed martensite islands during their formation. However, publications [16,17] have emphasized more complex mechanisms of BH in these steels as a result of the presence of the soft ferrite matrix and hard martensite phase in the microstructure and, in turn, the different behavior of phases during PS and the subsequent BH treatment.…”
mentioning
confidence: 99%